Quality of Life of Patients with Chronic Obstructive Pulmonary Disease Attending a Tertiary Care Hospital, Kavre, Nepal - Acharya Pandey, R.; Chalise, H. N.; Shrestha, A.; Ranjit, A. (Kathmandu University Medical Journal, 2021)
Background Chronic Obstructive Pulmonary Disease (COPD) is one of the most common chronic health conditions and is increasingly becoming a major public health problem among the elderly population. As the chronic obstructive pulmonary disease is not curable, evaluation of and methods to improve quality of life among such patients is of utmost importance. Objective The objective of the study was to assess the quality of life among patients living with chronic obstructive pulmonary disease. Method This is a cross-sectional carried out in Dhulikhel Hospital, Kathmandu University Hospital, Nepal in 2017-2018. A total of 274 patients aged 40 years and above were selected for this study. The quality of life of participants was assessed through the widely used shorter version ST George’s Respiratory Questionnaire (SGRQ-C). Result The mean age of the participants was 68.19 (SD ± 10.36) years, with the age range of 40–94 years. More than half (55.5%) of respondents were females, 55% were from rural areas, 42.7% were illiterate and 53.3% were from joint families. Agriculture (35.4%) and homemakers (32.5%) were the most prevalent occupation. The mean total score for all domains of quality of life was 68.06 (±18.87). The mean quality of life scores for symptom, activity, and impact domains was 70.11 (±22.33), 67.59 (±20.41), 67.64 (±20.41) respectively which suggested marked impairments in quality of life in all SGRQ-C domains. The symptoms and impact domains were most affected during the activity. Among socio-demographic variables, educational status, ethnicity, number of family members, type of family and economic status had a statistically significant effect on the quality of life. Initial health condition, smoking habit, number of cigarettes smoked, and years of smoking had statistically significant effects on quality of life. Conclusion Patients with chronic obstructive pulmonary disease have a low quality of life in three components of symptom, activity, and impact domains. Major factors associated with poor quality of life were low educational status, large family size, poor health condition, and smoking.